Substance and non-substance addiction - Zhang, Xiaochu; Shi, Jie; Tao, Ran (Internet addiction expert) (Springer, 2017)
This book focuses on the similarities and differences between substance and non-substance addictions. It discusses in detail the mechanisms, diagnosis and treatment of substance and non-substance addictions, and addresses selected prospects that will shape future studies on addiction. Addiction is a global problem that costs millions of lives tremendous damage year after year. There are mainly two types of addition: substance addiction (e.g., nicotine, alcohol, cannabis, heroin, stimulants, etc.) and non-substance addiction (e.g., gambling, computer gaming, Internet, etc.). Based on existing evidence, both types of addiction produce negative impacts on individuals' physical, mental, social and financial well-being, and share certain common mechanisms, which involve a dysfunction of the neural reward system and specific gene transcription factors. However, there are also key differences between these two types of addiction. Covering these aspects systematically, the book will provide researchers and graduate students alike a better understanding of drug and behavioral addictions.
Keywords: Substance abuse.; Substance abuse -- Treatment.; elektronické knihy; electronic books